Safe initiation of oral diets in hospitalized patients based on passing a 3-ounce (90 cc) water swallow challenge protocol - Leder, S.B.; Suiter, D.M.; Warner, H.L.; Acton, L.M.; Siegel, M.D. (QJM: An International Journal of Medicine, 2012)
Background: Safe and timely oral alimentation is crucial for optimum patient care.Objective: To determine the short-term success of recommending specific oral diets, including drinking thin liquids, to acute care hospitalized patients at risk for dysphagia based on passing a 3-ounce water swallow challenge protocol.Design: Prospective single group consecutively referred case series.Setting: Large, urban, tertiary care, teaching hospital.Participants: 1000 hospitalized patients.Intervention: 3-ounce (90 cc) water swallow challenge protocol.Measurements: Specific diet recommendations and volume (in cc) of liquid ingested at the next day's meal 12–24 h after passing a 3-ounce challenge protocol were accessed electronically from oral intake information entered on each participant's daily care logs. Eating and drinking success, clinically evident aspiration events and compliance with ordering the recommended diet were recorded. Care providers were blinded to the study's purpose.Results: Of 1000 patients, 907 met the inclusion criteria of stable medical, surgical or neurological conditions 12–24 h after passing a 3-ounce water swallow challenge protocol. All 907 were both eating and drinking thin liquids successfully and without overt signs of dysphagia. Median volume of liquid ingested was 340 cc [interquartile range (IQR), 240–460]. Specific diet recommendations were followed with 100% accuracy.Conclusions: A 3-ounce water swallow challenge protocol successfully identified patients who can be safely advanced to an oral diet without subsequent identification of overt signs of aspiration within 12–24 h of testing. Importantly, when a clinical 3-ounce challenge protocol administered by a trained provider is passed, specific diet recommendations, including drinking thin liquids, can be made safely and without the need for additional instrumental dysphagia testing.
Keywords: dept.cmd; peer-reviewed

The Auditory System and Its Interactions with the Visual System. - McCullagh, Jennifer; Nagle, S; Morse, D; Musiek, Frank E (Neuro-visual processing rehabilitation: An interdisciplinary approach, 2012)
Keywords: dept.cmd

Parsing pragmatics - Rivers, K.O.; Hyter, Y.D.; DeJarnette, G. (ASHA Leader, 2012)
Keywords: dept.cmd

Functional brain activation differences in school-age children with speech sound errors: speech and print processing - Preston, Jonathan L.; Felsenfeld, Susan; Frost, Stephen J.; Mencl, W. Einar; Fulbright, Robert K.; Grigorenko, Elena L.; Landi, Nicole; Seki, Ayumi; Pugh, Kenneth R. (Journal of Speech Language and Hearing Research, 2012)
Purpose: To examine neural response to spoken and printed language in children with speech sound errors (SSE). Method: Functional magnetic resonance imaging was used to compare processing of auditorily and visually presented words and pseudowords in 17 children with SSE, ages 8; 6[years; months] through 10; 10, with 17 matched controls. Results: When processing spoken words and pseudowords, the SSE group showed less activation than typically speaking controls in left middle temporal gyrus. They also showed greater activation than controls in several cortical and subcortical regions (e. g., left superior temporal gyrus, globus pallidus, insula, fusiform, and bilateral parietal regions). In response to printed words and pseudowords, children with SSE had greater activation than controls in regions including bilateral fusiform and anterior cingulate. Some differences were found in both speech and print processing that that may be associated with children with SSE failing to show common patterns of task-induced deactivation and/or attentional resource allocation. Conclusion: Compared with controls, children with SSE appear to rely more on several dorsal speech perception regions and less on ventral speech perception regions. When processing print, numerous regions were observed to be activated more for the SSE group than for controls.
Keywords: Brain; Cerebral Cortex; Child; Female; Functional magnetic resonance imaging (fMRI); Globus Pallidus; Gyrus Cinguli; Humans; Language Development Disorders; Magnetic Resonance Imaging; Male; Parietal Lobe; Phonetics; Photic Stimulation; Print processing; Reading; Speech; Speech Perception; Speech perception; Speech sound errors; Temporal Lobe; Visual Cortex; article; brain; brain cortex; child; cingulate gyrus; dept.cmd; female; globus pallidus; human; language disability; male; nuclear magnetic resonance imaging; parietal lobe; pathophysiology; phonetics; photostimulation; physiology; reading; speech; speech perception; temporal lobe; visual cortex

Auditory cortical processing in noise in normal-hearing young adults - Mccullagh, Jennifer; Musiek, Frank E; Shinn, Jennifer B (Audiological Medicine, 2012)
Objective: The ability to hear in background noise is related to the processing of the incoming acoustic signal in the peripheral auditory system as well as the central auditory nervous system (CANS). Electrophysiological tests have the ability to demonstrate the underlying neural integrity of the CANS, but to date a lack of literature exists demonstrating the effects of background noise on auditory cortical potentials. Therefore, the purpose of this investigation was to systematically investigate the effects of white noise on tone burst-evoked late auditory evoked potentials (N1, P2, and P3) in normal hearing young adults. Study Design: Twenty young-adult normal-hearing individuals served as subjects. A comparison of the late auditory evoked potentials (N1, P2, and P3) was made at multiple signal-to-noise ratios (SNRs) (quiet, + 20, + 10, 0). N1, P2, and P3 were elicited and both amplitude and latency were measured for each of the potentials. A standard oddball paradigm with binaural stimulation was used to evoke the potentials. Repeated Measures Analyses of Variance (ANOVA) were conducted for both the experimental factors of amplitude and latency with within subjects factors of condition (quiet, + 20, + 10, 0). Results: Results indicated no significant differences in N1, P2, or P3 amplitude or latency between the quiet and + 20 SNR condition; however, at poorer SNRs significant N1, P2, and P3 amplitude and/or latency differences were observed. Conclusion: The results indicate a change in higher-order neural function related to the presence of increased noise in the environment. © 2012 Informa Healthcare.
Keywords: Auditory evoked potentials; Central auditory processing; Hearing in noise; Late auditory evoked potentials; N1; P2; P3; Signal to noise ratio; adult; amplitude modulation; article; auditory nervous system; auditory stimulation; central nervous system; controlled study; dept.cmd; electrophysiology; evoked auditory response; female; hearing; human; human experiment; late auditory evoked potential; male; normal human; priority journal; sensory system electrophysiology; signal noise ratio